Provenance study of the limestone used in the construction and restoration of the Batalha Monastery (Portugal) - Schiavon, Nicola (2022)
To assess the provenance of the limestones used in the construction and restoration of the Batalha Monastery in central Portugal, stone samples collected from the monument and from five limestone quarries in the region surrounding the building were investigated by energy-dispersive X-ray fluorescence spectroscopy (ED-XRF), powder X-ray diffractometry (PXRD) and thermogravimetric analysis (TGA). Ca-Sr binary diagrams from the ED-XRF result indicated the source of the samples collected from different parts of the monastery. Thin-section observation supplemented the petrographic evidence for this identification. PXRD and TGA were also used to acquire information on the mineral and chemical composition of the stones. Preliminary results suggest that the monastery baluster was made of stone from the Valinho do Rei or Reguengo do Fetal quarries, whereas part of the church railing, the north-aisle eaves arch and Royal Cloister were made with stone from the Pidiogo or Cabeço do Roxo quarries.